Pengaruh Effective Tax Rate, Tunneling Incentive, dan Mekanisme Bonus terhadap Transfer Pricing - Salsabila, Leony; Lia Ira Sahara (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the effect of Effective Tax Rate, Tunneling Incentive, and Bonus Mechanism on Transfer Pricing. This is a quantitative study using secondary data obtained from the official website of the Indonesia Stock Exchange (IDX) in the form of annual financial statements. The sampling method used in this study is purposive sampling. From 84 companies in the food & beverage sub sector, a total sample of 15 companies was selected over a five-year period, resulting in 75 data observations. The analysis method employed is Panel Data Regression using EViews 12. The results show that effective tax rate, tunneling incentive, and bonus mechanism simultaneously have a significant effect on transfer pricing. However, partially, effective tax rate, tunneling incentive, and bonus mechanism has a significant effect on transfer pricing.